براہوئی خلکی شاعری ٹی موسم نا شیئراک: Seasonal Poetry in Brahui Folk Lore - Naz, Ghulam Hyder; Lehri, Inayatullah; Salah Uddin; Ajiz, Shah Muhammad (Al-Burz, 2012)
This article dials with Brahui folk lore. This portion of Brahui literature is richest then others. The natural and internal feelings have been focused in Brahui folk lore which is translated "Khalki Shairi" English. Brahui folk lores have verity and multi-dimensional thoughts regarding topics, rhymes, style and wordings. One of topic or part of Brahui Khalki poetry is called seasonal poetry. This type of poetry shows the values, aim of nomadic life and awareness of climate. This article end with discussion that rain fall, snow fall, cloudy, foggy, winter, summer, stream summer, and cold period the Brahui seasonal poetry replicate the inner opinion of life which is passing in between in this verity of weather..